Job interview skills (Rugeley : Focus Multimedia Limited, 2004)
Shows to handle job interviews through examples of interview questions with sample answers and tips for the interviewee.
Ελάχιστες απαιτήσεις συστήματος: Windows® 98/Me/NT/2000/XP; Pentium® III 500 or equivalent; 60MB hard drive; 128MB memory; 800x600x16bit colour; microphone and printer (recommended).
Keywords: CD-ROMs.; Interviewing -- CD-ROMs.